Analysis of Climate Variability and Trends in The Context of Climate Changes: Case Study in Terengganu - Othman, Wan Zunairah; Tukimat, Nurul Nadrah Aqilah; Azman, Azreen Harina; Rahmat, Siti Nazahiyah; Winarta, Bambang (International Journal of Integrated Engineering, 2022)
Uncertainty of climate extreme nowadays causes an alteration in the local climate trend and variability. Terengganu, Malaysia recorded series of extreme drought and flood events throughout a year affected by North-East monsoon which will change the next climate pattern. Thus, it will affecting the long-term planning and sustainability that related to the water resources in the long-term. The objective of this study was to analyse the trend changes of rainfall and temperature at Kuala Terengganu, Malaysia due to climate changes impact. The trends changes were analysed using Man-Kendall and Sen’s Slope. The climate projection result shows the annual mean temperature is expected to have decreasing trend until end of century. However Mar to June are expected to bit higher than historical reach to 29oC by RCP8.5. Then it will be dropped to 24oC (-5% from historical) during Northeast monsoon. Consistent to the annual rainfall, it was expected to have increasing trend over time. The highest increasing trend was expected to occur on Nov to Dec more than 40% by RCP8.5.